SISTEM CERDAS PEMANTAU HEWAN TERNAK PADA ALAM BEBAS BERBASIS INTERNET OF THINGS (IOT) - Galih Hendra Wibowo; Mohamad Dimyati Ayatullah; Junaedi Adi Prasetyo (Politeknik Negeri Malang, 2019)
One of the common problems experienced by animal farmers is heat stress or cold stress caused by changes in the environment. This resulted in a decrease in the productivity of livestock, cattle. Early monitoring needs to be done to avoid problems through monitoring tools for temperature, heart rate, and internet-based location of things (IoT). The monitor receives the value through the paired sensor and is sent to the web server. Users or breeders get information about the condition of farm animals and observe changes in value through graphs through the android application. The system built is able to receive values in a short interval time (10 seconds) so that the value obtained is the most recent value. Based on observations on the graph, the user can identify drastic changes, both decreases or increases, in the temperature and heart rate of the animal's condition and take precautions as early as possible.